ISA-2011B, a Phosphatidylinositol 4-Phosphate 5-Kinase α Inhibitor, Impairs CD28-Dependent Costimulatory and Pro-inflammatory Signals in Human T Lymphocytes - Kunkl, Martina; Porciello, Nicla; Mastrogiovanni, Marta; Capuano, Cristina; Lucantoni, Federica; Moretti, Chiara; Persson, Jenny L.; Galandrini, Ricciarda; Buzzetti, Raffaella; Tuosto, Loretta (Frontiers in Immunology, 2017)
Phosphatidylinositol 4,5-biphosphate (PIP2) is a cell membrane phosphoinositide crucial for controlling the activity of several proteins regulating cytoskeleton reorganization, cytokine gene expression, T cell survival, proliferation and differentiation. The main biosynthetic pathway of PIP2 involves phosphorylation of phosphatidylinositol 4-monophosphate (PI4P) at the D5 position of the inositol ring by phosphatidylinositol 4-phosphate 5-kinases (PIP5Ks). In human T lymphocytes, we have recently demonstrated that CD28 is the crucial costimulatory receptor that regulates PIP2 turnover by recruiting and activating PIP5Kα. We also found that PIP5Kα is the main regulator of both CD28 costimulatory signals integrating those delivered by TCR as well as CD28 autonomous signals regulating the expression of pro-inflammatory genes. Given emerging studies linking alterations of PIP2 metabolism to immune-based diseases, PIP5Kα may represent a promising target to modulate immunity and inflammation. Herewith, we characterized a recently discovered inhibitor of PIP5Kα, ISA-2011B, for its inhibitory effects on T lymphocyte functions. We found that the inhibition of PIP5Kα lipid-kinase activity by ISA-2011B significantly impaired CD28 costimulatory signals necessary for TCR-mediated Ca2+ influx, NF-AT transcriptional activity and IL-2 gene expression as well as CD28 autonomous signals regulating the activation of NF-κB and the expression of pro-inflammatory cytokines and chemokines. Moreover, our data on the inhibitory effects of ISA-2011B on CD28-mediated up-regulation of inflammatory cytokines related to Th17 cell phenotype in Type 1 diabetes (T1D) patients, suggest ISA-2011B as a promising anti-inflammatory drug.